The 21st century : photographs from the image collection - Goldberg, Susan; National Geographic (Washington, D.C.: National Geographic, 2021)
Spanning remarkable moments year-by-year from 2000 to 2021, this must-have collection presents 250 of the most impactful National Geographic images across print, digital and social media
Includes contributor information
Keywords: 2000-2099.; Documentary photography; National Geographic Society (U.S.) -- Photograph collections; Nature photography